1985
DOI: 10.1002/ar.1092120402
|View full text |Cite
|
Sign up to set email alerts
|

Mucosubstance histochemistry in control and acid‐stressed epidermis of brown bullhead catfish, lctalurus nebulosus (LeSueur)

Abstract: Glycoprotein components of epidermal mucous cells in control (pH 6.8) and acid-stressed (pH 5.8, 4.8, 4.0) brown bullhead catfish were studied by histochemical and autoradiographic methods. Following exposure to acid, increased numbers of epidermal mucous cells were noted in all tissue sites studied, particularly dorsal and ventral skin. Mucous cells of control fish and acid-stressed (pH 5.8) fish contained a mixture of neutral and acidic mucosubstances, the latter including both sialomucins and sulfomucins, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 40 publications
(38 reference statements)
2
20
0
Order By: Relevance
“…This might delay the damage due to the deleterious effects of the toxicants. Zuchelkowski et al (1985) also observed a n apparent shift towards increased sulfomucin production in the epidermal MCs of acid-stressed lctalurus nebulosus (Lesueur) and suggested that the functional significance of increased sulfomucin production may be related to maintenance of ionic equilibrium. Due to the active flow of water across the gills, which is necessary for respiration, the risk that slimy secretions of the opercular epidermis will be continuously washed away is also much greater than in the case of general body skin.…”
Section: Discussionmentioning
confidence: 89%
“…This might delay the damage due to the deleterious effects of the toxicants. Zuchelkowski et al (1985) also observed a n apparent shift towards increased sulfomucin production in the epidermal MCs of acid-stressed lctalurus nebulosus (Lesueur) and suggested that the functional significance of increased sulfomucin production may be related to maintenance of ionic equilibrium. Due to the active flow of water across the gills, which is necessary for respiration, the risk that slimy secretions of the opercular epidermis will be continuously washed away is also much greater than in the case of general body skin.…”
Section: Discussionmentioning
confidence: 89%
“…Mucus cell numbers have been shown to be sensitive to dietary changes, stress and handling in other Ictalurus species and to water temperature in channel catfish. 23,24 Work by our group has identified expression patterns of MUC2, MUC5AC, MUC19 and related isoforms in catfish gill. Examination of fish susceptible to the common freshwater pathogen, Flavobacterium columnare, revealed basally higher levels of goblet cells ( Fig.…”
Section: Mucins In the Gillmentioning
confidence: 99%
“…Nevertheless, Whitear and Mittal (53) conceived that such a shift could be related to a greater likelihood of infection in fresh water. In the skin of acid stressed catfish Ictalurus nebulosus, Zuchelkowski et al (61) found a shift towards increased production of sulphomucins and correlated this with the maintenance of ionic equilibrium.…”
Section: ) Sacciform Cellsmentioning
confidence: 99%
“…Previous studies have shown that principal constituents of mucus secreted by fish epidermis consists, in general, of macromolecules of complex and diversified natures including glycoproteins (GPs) (3,21,33,52,59,60,61). Different classes of GPs have been postulated to serve a variety of physiological activities in mammalian tissues (5,11,31,32,34,38,46,47,50).…”
mentioning
confidence: 99%